1987
DOI: 10.1136/sti.63.5.312
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of genital ulceration in the Gambia.

Abstract: SUMMARY The aetiology of genital ulceration was studied in 104 unselected patients (94 men, 10 women) attending a sexually transmitted disease (STD) clinic in the Gambia. Chancroid was diagnosed in 54 (52%), syphilis in 23 (22%), lymphogranuloma venereum (LGV) in seven (7%), and herpes in six (6%). In 28 (27%) patients no diagnosis was reached. Ten (10%) patients were found to have both chancroid and syphilis, three (3%) had both LGV and syphilis, and one (1 %) had both herpes and syphilis. Trimethoprim 160 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…In Africa, even in areas where syphilis is highly prevalent, most genital ulcers are due to chancroid. In the Gambia, a very similar frequency of aetiologies of genital ulcerations was found as had previously been reported from Swaziland, Nairobi and Johannesburg (Mabey et al 1987). It was also found that 10% of patients with genital ulcers had both chancroid and syphilis; in Nairobi both infections occured concurrently in 5% of patients with genital ulcers (D'Costa et al 1986).…”
Section: Chlamydia Trachomatis Infectionssupporting
confidence: 65%
“…In Africa, even in areas where syphilis is highly prevalent, most genital ulcers are due to chancroid. In the Gambia, a very similar frequency of aetiologies of genital ulcerations was found as had previously been reported from Swaziland, Nairobi and Johannesburg (Mabey et al 1987). It was also found that 10% of patients with genital ulcers had both chancroid and syphilis; in Nairobi both infections occured concurrently in 5% of patients with genital ulcers (D'Costa et al 1986).…”
Section: Chlamydia Trachomatis Infectionssupporting
confidence: 65%
“…These usually involved migrants or tourists from tropical regions. LGV is endemic in East and West Africa, India, Southeast Asia, and the Caribbean, where it reportedly causes 1–10% of all genital ulcers [10], [11].…”
Section: Epidemiologymentioning
confidence: 99%
“…It is the most common cause of sexually acquired genital ulceration in Africa, accounting for 80o of cases seen in Nairobi, Kenya (44), 52% of cases in The Gambia (35), more than 50o of cases in Johannesburg (15) and Durban (12), South Africa, and 39o of cases in Harare, Zimbabwe (32). The disease characteristically presents as painful ulcers of the genitalia which may often be found in association with painful regional lymphadenopathy.…”
Section: Introductionmentioning
confidence: 99%